Hubungan Stunting Dengan Karies Gigi Pada Anak Pra Sekolah di Posyandu Kel. Gunung Sulah Kota Bandar Lampung Provinsi Lampung - Alfah, Siti; Eni, St. Nur; Febriani, Tanti (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Short nutritional status or stunting is the condition of a person's height being less than normal based on age and gender. Height is a type of anthropometric examination and indicates poor nutritional status (malnutrition) over a long/chronic period of time. In developing the quality of human resources, the problem of stunting, which is one part of double burden malnutrition (DBM), has a very detrimental impact both in terms of health and in terms of economic productivity and in the short and long term. Malnutrition during this critical period can cause stunting and abnormal tooth growth and development and refers to enamel hypoplasia so that teeth are more susceptible to demineralization and caries. This study aims to determine the relationship between stunting and dental caries (def-t) in preschool children in Gunung Village. This research used a survey method with a cross-sectional approach which was carried out at the Posyandu, Gunung Sulah Village. Research sample of children 3 - 5 years old in Gunung Sulah Village who went to Posyandu. The instruments for this research were a recap sheet for dental caries examinations at Posyandu and a recap sheet of nutritional status/visit of toddlers to Posyandu. The data obtained was then analyzed by calculating the data frequency using the SPSS program. The research results showed that the prevalence of stunting was 9 people in the very short category (4.1%), 79 people in the short category (35.6%). The prevalence of dental caries is in the low category with 125 respondents (83.33%), the medium category with 22 respondents (14.66%) and the high category with 3 respondents (2%). Analysis of the relationship between stunting and dental caries (def-t) using Chi Square obtained a p - value = 0.000 (p - value < 0.05), so that statistically there is a relationship between short nutritional status (stunting) and dental caries (dmf-t ) in preschool children in Gunung Sulah Village, Way Halim District, Bandar Lampung City.